Mastering Endo-Laparoscopic and Thoracoscopic Surgery ELSA Manual - Lomanto, Davide; Chen, William Tzu-Liang; Fuentes, Marilou B. (Springer Nature, 2023)
This is an open access book. The book focuses mainly on the surgical technique, OR setup, equipments and devices necessary in minimally invasive surgery (MIS). It serves as a compendium of endolaparoscopic surgical procedures. It is an official publication of the Endoscopic and Laparoscopic Surgeons of Asia (ELSA). The book includes various sections covering basic skills set, devices, equipments, OR setup, procedures by area. Each chapter cover introduction, indications and contraindications, pre-operative patient's assessment and preparation, OT setup (instrumentation required, patient's position, etc.), step by step description of surgical procedures, management of complications, post-operative care. It includes original illustrations for better understanding and visualization of specific procedures. The book serves as a practical guide for surgical residents, surgical trainees, surgical fellows, junior surgeons, surgical consultants and anyone interested in MIS. It covers most of the basic and advanced laparoscopic and thoracoscopic surgery procedures meeting the curriculum and examination requirements of the residents.